Constraints to the capacity of smallholder farming households to adapt to climate change in South and Southeast Asia. (28th May 2019) - Brown, Peter R.; Afroz, Sharmin; Chialue, Lytoua; Chiranjeevi, T.; El, Sotheary; Grünbühel, Clemens M.; Khan, Iqbal; Pitkin, Cathy; Reddy, V. Ratna; Roth, Christian H.; Sacklokham, Silinthone; Williams, Liana J.
Abstract : Rural households in developing countries face a range of pressures to secure their livelihoods. Households feel the effects of changing rainfall patterns, droughts, cyclones, floods and increased temperatures, and draw on a wide range of resources to adapt but some households are better equipped than others. We explore the extent to which smallholder rural households might be able to adapt to the processes of increased climate variability or climate change through assessing their adaptive capacity using elements of the rural livelihoods framework. We involved almost 600 participants in discussions and interviews in India, Bangladesh, Cambodia and Lao PDR to explore the factors that condition their ability to adapt. We identified 36 key indicators of adaptive capacity, half were specifically related to climate change or climate variability, with others recognized as important in terms of overall livelihoods. "Experience", "health" and "labour" (Human capital), "access to market" and "farmer networks/groups" (Social capital) were considered strongly enabling of adaptation, whereas "lack of training" (Human capital) and "soil quality/condition" (Natural capital) constrained adaptation. It takes time for households to recover from climatic events, but, households with better access to diverse resources, and a more balanced livelihood portfolio were better able to cope. Mechanisms to support adaptation involved supporting farmer groups, novel information networks, better access to markets and value chains, land ownership, improved financial and economic management, and credit options.